PENGARUH MENGKONSUMSI MINUMAN MADU TERHADAP TINGKAT KEASAMAN PH SALIVA ANAK SEKOLAH DASAR - Dwi Eni Purwati; Siti Sulastri (Jurnal Kesehatan Gigi, 2016)
TITLEThe effect of honey water consumption to acidity level of pH saliva in elementary school childrenABSTRACTCommunities can take advantage of traditional medicine such as honey as an alternative medicine to reduce the formation of dental plaque. Honey containing antibiotics as antibacterial and antiseptic keeping the wound. Natural honey contains a lot of enzymes, that is very complex of protein molecul, produced by living cells and have function as catalyst, which is : The speed reaction modifier substance in the chemical process. The process happened within the body of every living beings. Based on preliminary studies to 10 students saliva examination average student salivary pH less than 7 below normal, and students have an average of dental caries 2. Research objective is to know the average level of acidity pH of saliva before and after drinking honey.Quasi-Experimental research type, research using pretest-posttest design With Control Group. Total sample of 60 students, by means of random sampling. Test analysis by T-Test.PH study results before and after drinking the honey of significance is p = 0.05 0.05. The conclusion of this study was there was the influence of drink honey to salivary pH values. Keywords : drink honey, the pH of saliva